Distinct disruptions in CA1 and CA3 place cell function in Alzheimer’s disease mice - Sanggeon Park; Mijeong Park; Eun Joo Kim; Jeansok J. Kim; Jeiwon Cho; Yeowool Huh (iScience)
Summary: The hippocampus, a critical brain structure for spatial learning and memory, is susceptible to neurodegenerative disorders such as Alzheimer’s disease (AD). Utilizing APPswe/PSEN1dE9 (APP/PS1) mice, we investigated neurophysiological mechanisms underlying AD-associated cognitive impairments by assessing place cell activities in CA1 and CA3 hippocampal subregions, which have distinct yet complementary computational roles. Analyses revealed significant deterioration in spatial representation capabilities of APP/PS1 relative to wild-type (WT) mice. Specifically, CA1 place cells exhibited reduction in coherence and spatial information, while CA3 place cells displayed reduction in place field size. Place cells in both subregions showed disruption in stability and burst firing properties. Furthermore, theta rhythm was significantly attenuated in CA1 place cells of APP/PS1 mice. These findings elucidate that distinct physiological perturbations in CA1 and CA3 place cells, coupled with disrupted hippocampal theta rhythmicity in CA1, potentially orchestrate the impairment of hippocampal-dependent spatial learning and memory in AD pathogenesis.